2006
DOI: 10.1111/j.1742-7843.2006.pto_507.x
|View full text |Cite
|
Sign up to set email alerts
|

Antispasmodic Effects of Rooibos Tea (Aspalathus linearis) is Mediated Predominantly through K+‐Channel Activation

Abstract: Rooibos tea has been widely used for abdominal spasm and diarrhoea. The aim of the present study was to explore the possible mechanism for its use in such ailments. Its aqueous extract (RT) at 0.3-10 mg/ml produced relaxation of spontaneous and low K π (25 mM)-induced contractions of rabbit jejunum, with weak effect on high K π (80 mM)-induced contractions. In the presence of glibenclamide, relaxation of low K π -induced contractions was prevented. Cromakalim inhibited contractions induced by low K π , but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 36 publications
0
58
0
Order By: Relevance
“…It showed a dose-dependent inhibitory effect on spontaneous contractions, thus showing that the observed antidiarrheal effect of the plant extract appears to be mediated through the presence of some gut relaxant component(s) in it. In our earlier studies, we observed that the spasmolytic effect of medicinal plants is usually mediated through K + channel opening (Gilani et al, 2005(Gilani et al, , 2006 or Ca ++ channel blockade (Bashir et al, 2011;Shah et al, 2011a). To assess, whether the spasmolytic effect of the crude extract of S. officinalis was also mediated via similar mechanism(s), it was tested on low K + (25 mM) and high K + (80 mM)-induced contractions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It showed a dose-dependent inhibitory effect on spontaneous contractions, thus showing that the observed antidiarrheal effect of the plant extract appears to be mediated through the presence of some gut relaxant component(s) in it. In our earlier studies, we observed that the spasmolytic effect of medicinal plants is usually mediated through K + channel opening (Gilani et al, 2005(Gilani et al, , 2006 or Ca ++ channel blockade (Bashir et al, 2011;Shah et al, 2011a). To assess, whether the spasmolytic effect of the crude extract of S. officinalis was also mediated via similar mechanism(s), it was tested on low K + (25 mM) and high K + (80 mM)-induced contractions.…”
Section: Discussionmentioning
confidence: 96%
“…To assess the involvement of K + channel opening (Gilani et al, 2006) and Ca ++ antagonist-like mechanisms (Bashir et al, 2011), the spasmolytic effect of the plant extract was tested on low K + (25 mM) and high K + (80 mM)-induced contractions in the isolated rabbit jejunum preparations. Following a sustained contraction in response to K + , the test material was added in a cumulative fashion to obtain the concentration-dependent inhibitory responses.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…Previous studies have shown that vasodilator response of vessel is usually mediated through K + channel opening or Ca ++ channel blockade [15]. In order to characterize, whether the vasorelaxant effect of TPPU was mediated via similar pathways, its relaxant efficacy was tested against low K + (25 mM) and high K + (80 mM)-induced contractions [19].…”
Section: Discussionmentioning
confidence: 99%
“…To explore the participation of K + channel opening and/or Ca ++ channel antagonist properties [15], the vasorelexant effect of TPPU was further studied against low K + (25 mM) and high K + (80 mM)-induced contractions, respectively.…”
Section: Animal Studiesmentioning
confidence: 99%
“…In the digestive tract, Ach activates nicotinic receptors, which are present in vegetative ganglia, or muscarinic receptors found on smooth muscles and parasympathetic nerve fibers [25]. The stimulation of muscarinic receptors on the membrane of smooth muscles increases the intracellular calcium concentration [26][27][28]. Muscarinic receptors in the smooth muscles induce signal transduction mediated by G-protein and activate phospholipase-C, resulting in the production of inositol-triphosphate and diacylglycerol.…”
Section: Discussionmentioning
confidence: 99%